The influence of academic pressure on adolescents’ problem behavior: Chain mediating effects of self-control, parent–child conflict, and subjective well-being - Jiang, Mao-min; Gao, Kai; Wu, Zheng-yu; Guo, Pei-pei (Frontiers in Psychology, 2022)
As a negative social issue, teenagers’ problem behavior not only affects individuals’ physical and mental health and social function development but is also not conducive to social harmony and stability. This study mainly discusses the influence of academic pressure on adolescents’ problem behavior, and the potential relationship between these and academic pressure, examining issues such as self-control, parent–child conflict, and subjective well-being. The data were collected from the fifth wave of the China Family Panel Studies (2017–2018). The data of 2,465 teenagers aged 10–15 were analyzed by LISREL8.8 software. The results show that academic pressure positively affects adolescents’ deviant behavior. The mediation model finds that parent–child conflict and self-control play a direct mediating role between academic pressure and adolescents’ behavioral problems. Parent–child conflict, self-control, and subjective well-being have important chain mediation effects between academic pressure and adolescents’ problem behavior. Therefore, in order to reduce the risk of such problems, it is necessary to further strengthen individuals’ ability to maintain self-control, promote or cultivate adolescents’ character strengths, create a harmonious family atmosphere, reduce the probability of parent–child conflict, and increase the subjective well-being of teenagers.